The development of menu ordering system using RF module: article / Saiful Fahmy Idham - Idham, Saiful Fahmy (2009)
A menu ordering system enables a customer to use a terminal device to order food, but can respond rapidly to changes and additions to the menu. The system may be used by a restaurant to facilitate ordering menu items by a customer to increase the effectiveness and efficiency to help both parties. When this system starts up, it transmits an operating program from main management equipment to each of a number of order-taking terminal devices. This project is to create a portable device with wireless connection between waiter and the kitchen using an RF Module with a microcontroller. The front end system with screen is for order takers that link to kitchen display and integrated with back end system that manages every menu system in a restaurant by handling orders, tracking payments, and alerting waiters when customers need assistance. The goal is to provide a reliable system that improves accuracy and efficiency of menu ordering.